0347 Insomnia and Quality of Life in Sleep Pattern: Sao Paulo Epidemiologic Sleep Study (EPISONO). (12th April 2019) - Lucena, Leandro R; Polesel, Daniel N; Poyares, Dalva; Bittencourt, Lia; Andersen, Monica L; Tufik, Sergio; Hachul, Helena
Abstract: Introduction: Sleep is essential for the individual's health and well-being and its deprivation brings serious physiological consequences. This study aimed to evaluate the sleep pattern through polysomnography in a general population considering the age groups and the influence of insomnia on quality of life. Methods: This cross-sectional study recruited volunteers randomly to represent the population of Sao Paulo, according to gender, age (20-80 years) and socioeconomic status. Data from polysomnography were used to assess sleep objectively and the WHOQOL-BREF questionnaire was used to assess quality of life scores. Using validated questionnaires based on Diagnostic and Statistical Manual of Mental Disorders, 4 th edition criteria, subjective insomnia was categorized in good sleepers, insomnia symptoms and insomnia syndrome. Anthropometric data, objective sleep parameters and quality of life were examined by range of decades of life in both genders. The same parameters were evaluated in subjective insomnia groups (in both men and women). Results: A total of 1, 042 participants were included, 574 women and 468 men. Groups with insomnia presented worse perception of quality of life compared to good sleepers in both genders. Women had a lower percentage of good sleepers (33.3%), as well as a higher percentage of insomnia symptoms (48.6%) and insomnia syndrome (18.1%) than men (42.1%, 47.2 % and 10.7%, respectively). Conclusion: Women presented more complaints about insomnia and lower perceived quality of life compared to men, especially in young ages. Men and women with insomnia symptoms or insomnia syndrome had a lower quality of life score. Support (If Any): This research was supported by fellowships from Associação Fundo de Incentivo à Pesquisa (AFIP), Coordenação de Aperfeiçoamento de Pessoal de Nível Superior (CAPES) - Finance Code 001 and Conselho Nacional de Desenvolvimento Científico e Tecnológico (CNPq).